Gambogic Acid Inhibits Gastric Cancer Cell Proliferation through Necroptosis - Shujun Wang; Yiping Wang; Hui Zhu; Miaohui Chen; Liang Zhang (Canadian Journal of Gastroenterology and Hepatology)
Gambogic acid (GA) is a natural xanthonoid secreted by Garcinia hanburyi tree. It possesses anti-cancer activity in various types of cancers. In gastric cancer, it inhibits cell proliferation through increasing apoptosis. However, whether necroptosis is involved in the GA-induced proliferation inhibited in gastric cancer is unknown. In the present study, we found that RIPK1 specific inhibitor necrostatin-1 (Nec-1) attenuated GA-induced proliferation inhibition. GA treatment increased the phosphorylation of necroptosis-related proteins, RIPK1, RIPK3, and MLKL, and their interactions to form the necrosome complex. The effector protein Drp-1 was dephosphorylated by GA treatment. Inhibition of necroptosis by different inhibitors and PGAM5 knockdown attenuated GA-induced cell death in gastric cancer cell lines, thereby attenuating GA-caused cell proliferation inhibition. All the data supported the conclusion that GA could inhibit gastric cancer cell proliferation by inducing necroptosis.